2018
DOI: 10.1017/thg.2018.6
|View full text |Cite
|
Sign up to set email alerts
|

Blood Eosinophil Count and Metabolic, Cardiac and Pulmonary Outcomes: A Mendelian Randomization Study

Abstract: Blood eosinophil count is associated with a variety of common complex outcomes in epidemiological observation. The aim of this study was to explore the causal association between determined blood eosinophil count and 20 common complex outcomes (10 metabolic, 6 cardiac, and 4 pulmonary). Through Mendelian randomization, we investigated genetic evidence for the genetically determined eosinophil in association with each outcomes using individual-level LifeLines cohort data (n = 13,301), where a weighted eosinophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…MR analysis helps to evaluate the causal relationship of WBC subtypes with lung function. To our knowledge, only one MR study investigated the association of circulating eosinophil counts with FEV 1 by using Netherlands LifeLines cohort data (n ¼ 13,301) and they did not find causal association [38], which was consistent with the current results. However, we found that genetically elevated total WBC and neutrophil counts were associated with decreased FVC and FEV 1 among the Asian population.…”
Section: Discussionsupporting
confidence: 89%
“…MR analysis helps to evaluate the causal relationship of WBC subtypes with lung function. To our knowledge, only one MR study investigated the association of circulating eosinophil counts with FEV 1 by using Netherlands LifeLines cohort data (n ¼ 13,301) and they did not find causal association [38], which was consistent with the current results. However, we found that genetically elevated total WBC and neutrophil counts were associated with decreased FVC and FEV 1 among the Asian population.…”
Section: Discussionsupporting
confidence: 89%
“…We are aware of one other MR study of eosinophil counts in relation to asthma, COPD, FEV 1 and FEV 1 /FVC, conducted entirely within the LifeLines cohort (N=13,301, 5 SNPs used as IVs). 16 In that study, confidence intervals for causal estimates of eosinophils were consistent with the null, albeit point estimates were consistent with a harmful effect for FEV 1 /FVC, asthma and COPD. Here, we used the largest eosinophil count GWAS to date (N=172,275) 14 to derive IVs, and found evidence for causality of eosinophils in reducing FEV 1 /FVC, the lung function trait in which impairment is the key feature of COPD diagnosis, and FEV 1 , the trait used to grade airflow limitation in COPD.…”
Section: Discussionmentioning
confidence: 68%
“…15 However, causality of these associations has yet to be established, with the only previous MR of lung function being of small sample size, with imprecise effect estimates precluding confident inference. 16 Moreover, causal effects of eosinophils on other respiratory phenotypes, such as asthma-COPD overlap (ACO), and respiratory infections are yet to be investigated. Diagnosis of COPD is made by spirometry if the ratio of the forced expiratory volume in one second (FEV 1 ) to the forced vital capacity (FVC), FEV 1 /FVC, is <0.7, with airflow obstruction being graded according to predicted values of FEV 1 .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated a potential causal effect of low surfactant protein D (SPD) in increasing COPD risk and progression using the MR framework. [12] Other molecules associated with COPD outcomes in epidemiological studies, such as C-reactive protein, [13] interleukin-6 [14] and blood eosinophil count, [15] do not yield evidence of causality when subjected to analysis by MR. Therefore, .…”
Section: Introductionmentioning
confidence: 99%